2006
DOI: 10.1614/wt-04-315r.1
|View full text |Cite
|
Sign up to set email alerts
|

Corn (Zea maysL.) Response to Trifloxysulfuron

Abstract: Experiments were conducted in weed-free environments to determine corn tolerance to trifloxysulfuron applied PRE or POST, and to determine the potential for trifloxysulfuron applied PRE or POST to cotton to injure corn grown in rotation the following year. Trifloxysulfuron at 3.75, 7.5, or 15 g ai/ha applied PRE or POST resulted in 98% stand reduction of imidazolinone-tolerant (IT) corn and 100% stand reduction in conventional corn. No injury occurred to imidazolinone-resistant (IR) corn. A corn cultivar yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In 2009, 'Honey Select' sweet corn was used and seemed to have enhanced injury response to the herbicides when compared to the field corn in 2008. Although trifloxysulfuron sodium has been shown to injure field corn in other studies (Porterfield & Wilcut, 2006), sweet corn has been shown to be more sensitive to herbicides when compared to field corn for several herbicides (Robinson, Monks, Schultheis, & Worsham, 1993;O'Sullivan, Zandstra, & Sikkema, 2002;Cavalieri et al, 2008;Nordby, Williams, Pataky, Riechers, & Lutz, 2008;Pataky, Meyer, Bollman, Boerboom, & Williams, 2008). Williams and Pataky (2010) reported that, despite a common genetic basis for herbicide metabolism, genotypic classes of sweet corn hybrids did not have identical field responses to 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitors herbicides, post-emergency application.…”
Section: Bioassaymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, 'Honey Select' sweet corn was used and seemed to have enhanced injury response to the herbicides when compared to the field corn in 2008. Although trifloxysulfuron sodium has been shown to injure field corn in other studies (Porterfield & Wilcut, 2006), sweet corn has been shown to be more sensitive to herbicides when compared to field corn for several herbicides (Robinson, Monks, Schultheis, & Worsham, 1993;O'Sullivan, Zandstra, & Sikkema, 2002;Cavalieri et al, 2008;Nordby, Williams, Pataky, Riechers, & Lutz, 2008;Pataky, Meyer, Bollman, Boerboom, & Williams, 2008). Williams and Pataky (2010) reported that, despite a common genetic basis for herbicide metabolism, genotypic classes of sweet corn hybrids did not have identical field responses to 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitors herbicides, post-emergency application.…”
Section: Bioassaymentioning
confidence: 99%
“…Since trifloxysulfuron sodium is most similar to flazasulfuron among herbicides used in turfgrass, it seems prudent to compare mobility of flazasulfuron with that of trifloxysulfuron sodium (Grey & McCullough, 2012). Flazasulfuron rates reduced corn height in preliminary studies and trifloxysulfuron sodium injured corn in field trials (Porterfield & Wilcut, 2006), so corn was chosen as the bioassay species. Our objective was to assess drift of flazasulfuron and trifloxysulfuron sodium using EPA guidelines for application conditions that match label specifications for each herbicide.…”
Section: Introductionmentioning
confidence: 99%
“…Acetolactate synthase (ALS)‐inhibiting herbicides are widely used in many crops, because they are effective in controlling a broad spectrum of weed species at low use rates, resulting in reduced environmental chemical loading (Wilcut et al. , 1996; Wright & Penner, 1998; Porterfield & Wilcut, 2006), and are residual in the soils of Israel (pH, 7.5–8.4). Most sulfonylurea herbicides remain stable in the soil for several months and can carry over to rotational crops (Johnson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Until the introduction of TFX, pyrithiobac was the only selective post‐emergence (POST) herbicide for annual broad‐leaved weed control that could be applied over the top in cotton and did not risk the yield (Culpepper et al. , 2000; Porterfield & Wilcut, 2006). Pyrithiobac and TFX are the only options for over the top POST application in tank mixtures for selective Cyperus rotundus L. (purple nutsedge) annual broad‐leaved weed control in non‐transgenic cotton cultivars.…”
Section: Introductionmentioning
confidence: 99%